The Inherent Tensions of “Instant Education”: A Critical Review of Mobile Instant Messaging - Pimmer, Christoph; Rambe, Patient (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
This paper critically reviews literature on the role of Mobile Instant Messaging (MIM) applications, such as WhatsApp, in supporting learning and teaching practice. Using formal qualitative synthesis as its methodology, and dialectical theory as an analytical framework, our main objective was to identify tensions, affordances, constraints, and resolution strategies in educational uses of MIM. In contrast to prior work, the analysis offers a nuanced and complex picture of the use of MIM in learning and teaching settings. Instead of facilitating the creation of educational outcomes in a straightforward manner, the realities of MIM use are socially constructed and the subject of conflictual negotiations. The educational use of MIM requires users to navigate the interdependent dialectical tensions of immediacy versus delays (temporal dimension), intimacy versus detachment (relationship dimension) and task versus ludic orientation (intellectual dimension). The findings also reveal a number of behavioural and technical resolution strategies that users deploy to manage these tensions.